Adil Dalam Poligami Menurut Kyai Di Jombang Perspektif M. Quraish Shihab - Ahmad Khotim (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang Indonesia, 2019)
This article reviews about M. Quraish Shihab's perspective polygamy, and the one who practices polygamy is a Kyai in Jombang Regency. The status of polygamy has been registered at the Jombang M. Quraish Shihab Religious Court, seeing that justice can only be in the matter of matei, while being fair in matters of affection is very difficult to apply to people who are polygamous. Whereas the Kyai in Jombang who do polygamy can all only be fair in material matters, if in terms of affection it is very difficult to do this in line with the view of M. Quraish Shihab.